ONJ (MRONJ) Update 2021-Osteonecrosis of Jaw Related to Bisphosphonates and Other Drugs-Prevention, Diagnosis, Pharmacovigilance, Treatment: A 2021 Web Event - Vittorio Fusco; Giuseppina Campisi; Paola Carcieri; Franca Fagioli; Oscar Bertetto; Michele Davide Mignogna; Alberto Bedogni (MDPI AG, 2022)
On the 8th and 9th of May 2021, an online conference was organized to connect Italian physicians, dentists and oral care specialists, students, nurses, psychologists, dental hygiene experts, and other professionals to discuss controversial issues about Medication-Related Osteonecrosis of Jaw (MRONJ). The first section evaluated differences between Italian recommendations, released on 2020 by Italian Societies of Oral Pathology and Medicine (SIPMO) and Maxillofacial Surgery (SICMF), and other international practice guidelines or documents. A first round table gathered expert opinions about MRONJ definitions and staging systems. Another round table was dedicated to opinion of drug prescribers (oncologists, hematologists, rheumatologists, and other physicians treating osteoporosis). Educational sessions illustrated the main differences between previous (2013) and more recent (2020) Italian recommendations. A large space was dedicated to the presentation of scientific contributions from centers in Italy, divided in specific sessions (epidemiology; case series; special case reports; prevention experiences; MRONJ treatment). Conclusions: in an innovative web conference, talks and scientific reports underlined importance of adequate imaging study of bone in definition and staging of MRONJ cases, the role of surgery in treatment of the disease, and the value of oral hygiene in the prevention.